2020
DOI: 10.1029/2019gl086527
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic Acceleration Sustains Ganymede's Footprint Tail Aurora

Abstract: Integrating simultaneous in situ measurements of magnetic field fluctuations, precipitating electrons, and ultraviolet auroral emissions, we find that Alfvénic acceleration mechanisms are responsible for Ganymede's auroral footprint tail. Magnetic field perturbations exhibit enhanced Alfvénic activity with Poynting fluxes of ~100 mW/m2. These perturbations are capable of accelerating the observed broadband electrons with precipitating fluxes of ~11 mW/m2, such that Alfvénic power is transferred to electron acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 61 publications
6
60
1
Order By: Relevance
“…Using this relation, for the frequency range between 0.2 and 800 Hz, the corresponding parallel wavelengths are cascaded from ~20 to 10 −3 R J . These Alfvénic magnetic signatures together with measurements of broadband precipitating electron fluxes in Figure 2e are also a characteristic feature of Alfvénic acceleration associated with footprint tail aurorae (Szalay, Allegrini et al, 2020; Szalay et al, 2018).…”
Section: Interpretation and Discussionsupporting
confidence: 52%
“…Using this relation, for the frequency range between 0.2 and 800 Hz, the corresponding parallel wavelengths are cascaded from ~20 to 10 −3 R J . These Alfvénic magnetic signatures together with measurements of broadband precipitating electron fluxes in Figure 2e are also a characteristic feature of Alfvénic acceleration associated with footprint tail aurorae (Szalay, Allegrini et al, 2020; Szalay et al, 2018).…”
Section: Interpretation and Discussionsupporting
confidence: 52%
“…Therefore, the error on the source size and on the ensuing results (electron energy and beaming angle ) should be very small. Szalay et al (2020a) showed that in this present case, Ganymede's footprint tail is sustained by Alfvénic acceleration processes. Thus, as suggested by Louarn et al (2018), all the radio emissions seem to be triggered by Alfvénic acceleration (as at Earth, Su et al, 2007).…”
Section: 1029/2020gl090021supporting
confidence: 51%
“…In conclusion, we analyzed the first example of in situ particle measurements of a Ganymede-induced radio emission, during the Ganymede's tail flux tube crossing (Szalay et al, 2020a) connected to FUV emission. Looking at the distribution functions before, during, and after the source crossing, we showed that the loss cone-driven CMI can explain the generation of decametric radio emission.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ions are also accelerated, most likely from Alfvénic interactions, closer to Io (Szalay et al, 2020). And finally, the first report of in situ electron measurements during a Ganymede FPT crossing suggests that Alfvén waves accelerate the electrons that create the tail (Szalay et al, 2020a). This recent body of evidence supports the argument that Aflvénic acceleration sustains satellite FPTs.…”
Section: Introductionmentioning
confidence: 99%